Prevalence of inherited metabolic disorders among newborns in Zhuzhou, a southern city in China - Luo, Hunjin; Wang, Jiqing; Chen, Junfeng; Yi, Huijian; Yang, Xiaodong; Peng, Yao; Ni, Liu; Yang, Yi-Qiong; Zhang, Xiao-Min; Huang, Hongping (Frontiers in Genetics, 2024)
Background and aims: Defective enzymes, cofactors, or transporters of metabolic pathways cause inherited metabolic disorders (IMDs), a group of genetic disorders. Several IMDs have serious consequences for the affected neonates. Newborn screening for IMDs is conducted by measuring specific metabolites between 3 and 7 d of life. Herein, we analyzed the incidence, spectrum, and genetic characteristics of IMDs in newborns in the Zhuzhou area.Methods: Tandem mass spectrometry was conducted on 90829 newborns who were admitted to the Women and Children Healthcare Hospital of Zhuzhou and requested for screening for IMDs.These newborns were subsequently subjected to next-generation sequencing and further validated using Sanger sequencing.Results: 30 IMDs cases were found in 90829 cases of newborns screened for IMDs, and the overall incidence was 1/3027. The incidence of amino acid, organic acid, fatty acid oxidation and urea cycle disorders were 1/8257、 1/18165、 1/7569、 and 1/45414, respectively. Additionally, 9 cases of maternal IMDs were found in our study, and unreported gene mutations of 3 cases IMDs were identified.Our data indicated that IMDs are never uncommon in zhuzhou, meanwhile，we also found that primary carnitine deficiency was the only disorder of fatty acid oxidation in Zhuzhou， and the incidence (1/7569) was higher than the national level，organic acid metabolic diseases are mostly inherited. Therefore, our study has clarified the disease spectrum and genetic backgrounds, contributing to the treatment and prenatal genetic counseling of these disorders in this region.